Controlled randomised crossover trial of the effects of physiotherapy on mobility in chronic multiple sclerosis. Issue 2 (1st February 2001) - Wiles, C M; Newcombe, R G; Fuller, K J; Shaw, S; Furnival-Doran, J; Pickersgill, T P; Morgan, A
Abstract : OBJECTIVES: To determine whether physiotherapy can improve mobility in chronic multiple sclerosis and whether there is a difference between treatment at home and as a hospital outpatient? METHODS: A randomised controlled crossover trial was undertaken in patients with chronic multiple sclerosis who had difficulty walking and were referred from neurology clinics: allocation was to one of six permutations of three 8 week treatment periods separated by 8 week intervals: treatments consisted of physiotherapy at home, as an outpatient, or "no therapy". The main outcome measures were based on independent assessments at home and included mobility related disability (primary outcome: the Rivermead mobility index), gait impairments, arm function, mood, and subjective patient and carer ratings. Therapy was assessed by recording delivery, achievement of set targets, patient and carer preference, and cost. RESULTS: On the Rivermead mobility index (scale 0–15) (primary outcome) there was a highly significant (p<0.001) treatment effect of 1.4–1.5 units favouring hospital or home based therapy over no therapy: this was supported by other measures of mobility, gait, balance, and the assessor's global "mobility change" score: there was no major difference between home and hospital. Carers preferred home treatment but neither they nor patients discerned greater benefit there. Estimated costs of home physiotherapy were £25/session and those at hospital were £18 (including £7 patient travel costs). CONCLUSION: A course of physiotherapy is associated with improved mobility, subjective wellbeing, and improved mood in chronic multiple sclerosis compared with no treatment but benefit may only last a few weeks: there is little to choose between home and hospital based therapy but the first is more costly, mainly due to skilled staff travelling time.